Perancangan dan Pengembangan Aplikasi Pengaduan Masyarakat Desa Karangmalang Berbasis Web dan Mobile - Mcdarayan, Naki Beneficient Juan Gracin; Ikrimach (Jurnal Informatika Ekonomi Bisnis, 2025)
This research aims to design and develop a web and mobile-based public complaint application in Karangmalang Village, Kasreman District, Ngawi Regency. The main problem faced is the manual complaint reporting process, which leads to delays and lack of transparency in handling public issues. The study applies the software engineering approach using the waterfall model, consisting of requirement analysis, system design, implementation, and testing. The application was developed using Flutter for the user interface, Node.js for the backend, and MySQL as the main database. Black-box testing results indicate that all system functions operate effectively according to user requirements, including reporting, status tracking, and complaint management features for village administrators. This system enables citizens to submit complaints quickly and allows the village government to respond more efficiently and systematically. In conclusion, the application enhances transparency and accountability in public service delivery at the village level, while strengthening collaboration between citizens and the local government in problem-solving processes.